Optimization of DNA recovery and amplification from non-carbonized archaeobotanical remains. - Nathan Wales (Public Library of Science (PLoS), 2014)
Ancient DNA (aDNA) recovered from archaeobotanical remains can provide key insights into many prominent archaeological research questions, including processes of domestication, past subsistence strategies, and human interactions with the environment. However, it is often difficult to isolate aDNA from ancient plant materials, and furthermore, such DNA extracts frequently contain inhibitory substances that preclude successful PCR amplification. In the age of high-throughput sequencing, this problem is even more significant because each additional endogenous aDNA molecule improves analytical resolution. Therefore, in this paper, we compare a variety of DNA extraction techniques on primarily desiccated archaeobotanical remains and identify which method consistently yields the greatest amount of purified DNA. In addition, we test five DNA polymerases to determine how well they replicate DNA extracted from non-charred ancient plant remains. Based upon the criteria of resistance to enzymatic inhibition, behavior in quantitative real-time PCR, replication fidelity, and compatibility with aDNA damage, we conclude these polymerases have nuanced properties, requiring researchers to make educated decisions as to which one to use for a given task. The experimental findings should prove useful to the aDNA and archaeological communities by guiding future research methodologies and ensuring precious archaeobotanical remains are studied in optimal ways, and may thereby yield important new perspectives on the interactions between humans and past plant communities.